2006
DOI: 10.1029/2006gl027509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and atmospheric pressure on methane (CH4) ebullition from near‐surface peats

Abstract: [1] Recent studies suggest that ebullition of biogenic gas bubbles is an important process of CH 4 transfer from northern peatlands into the atmosphere and, as such, needs to be better described by models of peat carbon dynamics. We develop and test a simple ebullition model in which a threshold gas volume in the peat has to be exceeded before ebullition occurs. The model assumes that the gas volume varies because of gas production and variations in pressure and temperature. We incubated peat cores in the labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
123
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(134 citation statements)
references
References 12 publications
10
123
0
Order By: Relevance
“…Briefly, the simulated aqueous CH 4 concentration in each soil level is used to estimate the expected equilibrium gaseous partial pressure as a function of temperature and pressure. When this partial pressure exceeds C e,max (taken as 15 % of the ambient pressure; Baird et al, 2004;Strack et al, 2006;Wania et al, 2010), bubbling occurs to remove CH 4 to below this value, modified by the fraction of CH 4 in the bubbles (taken as 57 %; Kellner et al, 2006;Wania et al, 2010). Bubbles are immediately added to the surface flux for saturated columns and are placed immediately above the water table interface in unsaturated columns.…”
Section: Ebullitionmentioning
confidence: 99%
“…Briefly, the simulated aqueous CH 4 concentration in each soil level is used to estimate the expected equilibrium gaseous partial pressure as a function of temperature and pressure. When this partial pressure exceeds C e,max (taken as 15 % of the ambient pressure; Baird et al, 2004;Strack et al, 2006;Wania et al, 2010), bubbling occurs to remove CH 4 to below this value, modified by the fraction of CH 4 in the bubbles (taken as 57 %; Kellner et al, 2006;Wania et al, 2010). Bubbles are immediately added to the surface flux for saturated columns and are placed immediately above the water table interface in unsaturated columns.…”
Section: Ebullitionmentioning
confidence: 99%
“…Evidence of this has been found in both laboratory (Baird et al, 2004;Kellner et al, 2006) and field (Strack et al, 2005) experiments. Baird et al (2004) found a threshold gas content limit of approximately 10-14% while Kellner et al (2006) found threshold values of 12 and 15% provided very good results when modelling ebullition events.…”
Section: Carbon Cycling and Ecohydrologymentioning
confidence: 66%
“…Evidence of this has been found in both laboratory (Baird et al, 2004;Kellner et al, 2006) and field (Strack et al, 2005) experiments. Baird et al (2004) found a threshold gas content limit of approximately 10-14% while Kellner et al (2006) found threshold values of 12 and 15% provided very good results when modelling ebullition events. These gas bubbles also affect the hydrological properties of peat since as bubbles form, they block off voids, and have the potential to greatly reduce water and solute transfer from surrounding areas , creating a localized zone of over-pressuring (Kellner et al, 2004).…”
Section: Carbon Cycling and Ecohydrologymentioning
confidence: 66%
“…Somewhat similar ebullitions occur in natural systems, such as saturated sediment (Winterwerp et al 2004;Amos and Mayer 2006), peatlands (Tokida et al 2005;Kellner et al 2006), and in gas-driven eruptions for some types of volcanic activity (Gaonach et al 1996;Lovejoy et al 2004;Stix 2007), and lake and ocean activities (Zhang and Kling 2006). Strack et al (2005) described what could be essentially the same behavior as "potential episodic release of CH4 via ebullition events."…”
Section: Introductionmentioning
confidence: 92%